A New Aerophilic Neidium Pfister (Neidiaceae, Bacillariophyta) species from Guangxi Zhuang Autonomous Region, China - Liu, Yan; Kociolek, John Patrick; Liu, Qi; Tan, Xiang; Fan, Yawen (Phytotaxa, 2020)
A new Neidium species was observed from a wet-wall in Shiwan Mountains National Forest Park, Guangxi Zhuang Autonomous Region, in the Southwest of China. This region of China has not had much previous attention focused on the biodiversity of freshwater algae. The new species, Neidium convolutum Y.Liu & Kociolek, is very distinctive compared with other known Neidium species, having torsion of the valves along the apical axis, large linear valves with wedge-shaped apices, oblique striae and volate occlusions in the areolae. We present a formal description of this species based on both light and scanning electron microscopic observations, and compare it with other, morphologically-similar species.